Characterization of wine astringency contributed by acetaldehyde-mediated condensation between flavan-3-ols and grape skin/seeds polyphenol - WANG,Lixia (2022)
Abstract Since the grape skin and seed contain different phenolic substances, the proportion of the skin and seed will affect the wine mouthfeel during the wine making process. During the wine ageing, the interaction between flavanols with anthocyanins is an important reaction and considered linked to astringency. Hence, a major question is whether changing the skin-seed ratio will affect the polymerization of phenolic substances in wine, thus affecting the astringency of wine. To answer this, astringency of wine was studied by changing the content of grape skins and seeds by SDS-PAGE, fluorescence quenching and sensory taste. Besides, acetaldehyde-mediated condensation reaction between different flavan-3-ols and malvidin-3-glucoside were studied in model solution. The result showed that grape skins and seeds contribute differently to astringency sensation, mainly because of the difference in the type and content of flavanols and anthocyanins contained in them. In addition, acetaldehyde-induced flavan-3-ols: anthocyanin mixture presents a strong effect toward the interaction with BSA when compared to other phenolic combinations. Furthermore, it was observed that the protein-binding ability of the polyphenols in red wine has a strong correlation with the wine astringency intensity.